2021
DOI: 10.3390/nano11030767
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of π-SnS Nanoparticles and Corresponding Thin Films

Abstract: Tin sulfide polymorph (π-SnS) nanoparticles exhibit promising optoelectrical characteristics for photovoltaic and hydrogen production performance, mainly because of the possibility of tuning their properties by adjusting the synthesis conditions. This study demonstrates a chemical approach to synthesize π-SnS nanoparticles and the engineering of their properties by altering the Sn precursor concentration (from 0.04 M to 0.20 M). X-ray diffraction and Raman studies confirmed the presence of pure cubic SnS phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Basically, SnS exhibits p-type conductivity under Sn-poor conditions, but n-type under Sn-rich conditions. 38 Herein, the deposited TS thin film exhibits n-type semiconductor properties, which may be due to trace Sn compensation which supports the EDX data. The results of the Hall effect measurement for comparison of the electrical properties among TS, TSSe and TSe thin films are displayed through Fig.…”
Section: Electrical Studiessupporting
confidence: 80%
“…Basically, SnS exhibits p-type conductivity under Sn-poor conditions, but n-type under Sn-rich conditions. 38 Herein, the deposited TS thin film exhibits n-type semiconductor properties, which may be due to trace Sn compensation which supports the EDX data. The results of the Hall effect measurement for comparison of the electrical properties among TS, TSSe and TSe thin films are displayed through Fig.…”
Section: Electrical Studiessupporting
confidence: 80%
“…The band at 312 cm −1 in the Raman spectrum also revealed the presence of the SnS 2 phase [55,58] . However, the existence of this phase was not observed in PXRD; only cubic SnS was identified, Figure S4 red curve, S7 black curve [59–63] . The discrepancy between Raman and PXRD results can be rationalized by involving photochemical oxidation of SnS to SnS 2 and the formation of SnO 2 that occurred under intense laser irradiation when the Raman spectra were measured.…”
Section: Resultsmentioning
confidence: 97%
“…[55,58] However, the existence of this phase was not observed in PXRD; only cubic SnS was identified, Figure S4 red curve, S7 black curve. [59][60][61][62][63] The discrepancy between Raman and PXRD results can be rationalized by involving photochemical oxidation of SnS to SnS 2 and the formation of SnO 2 that occurred under intense laser irradiation when the Raman spectra were measured. Even though tin sulfide NPs could be synthesized in aqueous medium without silicate, the resulting NPs were heterogeneous and unstable as both the oxidation and aggregation quickly took place.…”
Section: Tin Sulfidementioning
confidence: 99%
“…Narrow bandgap SnS semiconductor nanomaterials, composed of low-cost, earth abundant, and eco-friendly elements, have a strong optical activity in the near-infrared (NIR) and infrared (IR) regions which have great potentials in the field of NIR photodetectors and biomedical applications. [42][43][44] 0D nanoparticles have a size range from 1 to 100 nm, which have received intensive attention in the past two decades in many fields, such as energy storage and conversion, catalysis, optoelectronics, sensors, and biomedicines, due to their quantum effect. [33,34,36] Until now, a number of approaches have been employed to synthesize the 0D SnS nanomaterials with narrow size distribution.…”
Section: Synthesis Of 0d Sns Nanomaterialsmentioning
confidence: 99%
“…[33,34,36] Until now, a number of approaches have been employed to synthesize the 0D SnS nanomaterials with narrow size distribution. [31,[42][43][44][45][46][47][47][48][49][50] For example, in 2010, Ning et al [47] reported 0D SnS NPs by a solvothermal method using Sn 6 O 4 (OH) 4 as a Sn source and TAA as a S source. By strictly controlling the molar ratio of Sn to S, the 0D SnS NPs with uniform distribution can be obtained, as shown in Figure 2a.…”
Section: Synthesis Of 0d Sns Nanomaterialsmentioning
confidence: 99%